CHARACTERIZATIONS OF h -HEMIREGULAR AND h -SEMISIMPLE HEMIRINGS BY INTERVAL VALUED ( , ) q -FUZZY h -IDEALS - Mahmood, T. (The Nucleus, 2014)
In this paper we define interval valued ( , ) q -fuzzy h-subhemirings, interval valued ( , ) q -fuzzy interior h-ideals, interval valued ( , ) q -fuzzy prime h-ideals, interval valued ( , ) q -fuzzy semiprime h-ideals. We characterize hhemiregular and h-semisimple hemirings by the properties of these interval valued ( , ) q -fuzzy h-ideals. Keywords: Interval valued ( , ) q -fuzzy h-ideals, interval valued ( , ) q -fuzzy interior h-ideals, interval valued ( , ) q -fuzzy prime h-ideals, interval valued ( , ) q -fuzzy semiprime h-ideals, h-hemiregular, h-semisimple hemirings.